Effects of iron sources and doses on plant growth criteria in soybean seedlings - Füsun Gülser (Eurasian Journal of Soil Science, 2019)
In this study, effects of different iron sources and doses on plant growth criteria in soybean (Glycine max L.) seedlings were investigated. The experiment was conducted according to factorial experimental design with three replications under controlled conditions. Atakişi variety of soybean (Glycine max L.) cultivar was used as a plant material. Three soybean seeds were sown each plastic pot having 1.3 kg soil:sand mixed in 1:1 ratio. Three different Fe sources (FeSO4.7H2O, Fe-EDDHA and nanoFe) were applied to the pots with three different doses (0-15-30 mg Fe kg-1). The experiment was ended after five weeks of seed sowing. Shoot length, shoot fresh and dry weights, root length, root fresh and dry weights and number of compound leaf in soybean seedlings were determined at the end of the experiment. The highest shoot fresh and dry weights, root fresh and dry weights, compound leaf number were determined in 15 mg kg-1 nano Fe applications as 3.56 g, 0.83 g, 2.30 g, 0.33 g and 5, respectively. Increasing the application dose of nano-Fe from 15 to 30 mg kg-1 caused to decrease in fresh and dry weights in soybean seedlings. Generally, shoot growth decreased and root length increased in soybean seedlings by increasing Fe application doses. Seedling growth in soybean generally increased depend on the Fe sources in the following order; FeSO4.7H2O < Fe-EDDHA < nano-Fe.